Pediatric ophthalmology surgery and procedures tricks of the trade - Yoo, Sylvia H. (Thieme, 2021)
"Children can be affected by a wide range of ophthalmic disorders, many of which require surgical intervention. Pediatric Ophthalmology Surgery and Procedures: Tricks of the Trade by esteemed pediatric ophthalmologist Sylvia Yoo and expert contributors covers the full range of pediatric ophthalmic procedures. As with other titles in this series, the book is consistently formatted with concise, step-by-step guidance. Chapters include goals, advantages, expectations, key principles, indications, contraindications, preoperative preparation, surgical planning, perioperative tips and pearls, operative technique and tools, what to avoid, complications, and postoperative care"--